The Transformation of Monkey King: A Semiotic Perspective - Yang, Lei; Dechsubha, Thawascha (Technium Social Sciences Journal, 2022)
The Journey to the West, based on the story of Chen Xuanzang’s learning from the scriptures in the Tang Dynasty, was finally written by Wu Cheng’en in the Ming Dynasty, which deeply reflected the social reality at that time. It was not only the first romantic novel about ghosts and gods in ancient China, but also a masterpiece of romanticism in the history of world literature. The hero of the story, Monkey King, has been constantly mythologized in the process of China’s folk communication, becoming a household name hero and a cultural sign. Taking the Monkey King as the research object, this paper discusses its cross-media transformation from the perspective of semiotics, in order to provide some reference for China’s excellent traditional literature to go out.